2012
DOI: 10.5713/ajas.2011.11359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Glutamine on Growth Performance, Plasma Parameters and LPS-induced Immune Response of Weaned Barrows after Castration

Abstract: Two experiments were conducted to investigate the effects of supplemental glutamine on growth performance, plasma parameters and LPS-induced immune response of weaned barrows after castration. In experiment 1, forty-eight weaned male piglets were used and fed maize and soybean meal diets supplemented with 0 (Control) or 2% L-Gln (Gln+) for 25 days. The results indicated that the Gln+ group tended to increase average daily gain compared to control in stages of days 7 to 14 and 0 to 25. The Gln+ had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Lipopolysaccharide (LPS) is an integral component of the outer cell membranes of Gram-negative bacteria which are shed from the bacteria when cell lysis occurs [ 40 ]. E. coli K88 produces LPS [ 41 ], which induced endotoxic shock by triggering the systemic inflammatory response [ 42 45 ]. The endotoxins from LPS induce a degenerative morphology and the destruction of lymphocytes in birds [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is an integral component of the outer cell membranes of Gram-negative bacteria which are shed from the bacteria when cell lysis occurs [ 40 ]. E. coli K88 produces LPS [ 41 ], which induced endotoxic shock by triggering the systemic inflammatory response [ 42 45 ]. The endotoxins from LPS induce a degenerative morphology and the destruction of lymphocytes in birds [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The birds fed diets supplemented with 1% Gln had higher IgA concentrations in the intestines and thus may have been more resistant to infection. 24 Hsu et al 35 showed that dietary provision of 2% Gln was essential for the maintenance of gut-associated lymphoid tissues and for s-IgA synthesis by the small intestine. Production of s-IgA appears to be a limiting factor in mucosal immunity, as a reduction in s-IgA was experimentally associated with functional deficits in established immunity against various viruses and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moeser et al (2007) highlights the importance of optimizing nutrition and the immune status to help animals cope with weaning stresses. In this regard, the supplementation of Gln, a NEAA, has shown promising results in mice (Rogero et al, 2011;Sellmann et al, 2015) and pigs (Lee et al, 2003;Hsu et al, 2012). Moreover, Duttlinger et al (2020) demonstrated a potential to replace antibiotics with Gln to alleviate weaning and transportation stresses.…”
Section: Introductionmentioning
confidence: 99%